Impact of bifurcation lesion on 10-year mortality in the SYNTAX trial. (3rd October 2022) - Ninomiya, K; Serruys, P W; Garg, S; Gao, C; Masuda, S; Lunardi, M; Burzotta, F; Morice, M C; Colombo, A; Mack, M J; Holmes, D R; Davierwala, P M; et al.
Abstract: Background: Percutaneous coronary intervention (PCI) of bifurcation lesions is associated with higher rates of adverse events, and currently it is unclear whether PCI or coronary artery bypass grafting (CABG) is the safer treatment for these patients at very long-term follow up. Objectives: To investigate the impact of bifurcation lesions on observed all-cause 10-year mortality in the SYNTAX trial. Methods: In the SYNTAX Extended Survival study, 10-year observed mortality was compared among four groups: (a) presence of ≥1 bifurcation lesion and treatment with PCI (n=649), (b) no bifurcation lesion and treatment with PCI (n=248), (c) presence of ≥1 bifurcation lesion and treatment with CABG (n=651), and (d) no bifurcation lesion and treatment with CABG (n=239). Results: Compared to patients without bifurcations, those with bifurcation lesion(s) treated with PCI had a significantly higher risk of all-cause death (19.8% vs 30.1%; HR: 1.55, 95% CI: 1.12 to 2.14; p=0.007), whereas following CABG, mortality was similar in patients with or without bifurcation lesion(s) (23.3% vs 23.0%; HR: 0.81, 95% CI: 0.59 to 1.12; p=0.207). (Figure1) There was a significant interaction between bifurcation lesion(s) and treatment arm (p for interaction=0.006). In PCI patients, at 5-years there was no significant difference in mortality between 1- vs 2-stent techniques, whereas at 10-years, a 2-stent technique was associated with higher mortality (33.3% vs 25.9%; HR: 1.51, 95% CI: 1.06 to 2.14; p=0.021, Figure2). Conclusions: Bifurcation lesion(s) require special attention from the heart team discussion, considering the higher 10-year all-cause mortality associated with PCI. Careful evaluation of bifurcation lesion complexity may be helpful in decision-making. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The SYNTAX Extended Survival study was supported by the German Foundation of Heart Research (Frankfurt am Main, Germany). The SYNTAX trial, during 0-5 years follow-up, was funded by Boston Scientific Corporation (Marlborough, MA, USA). Both sponsors had no role in the study design, data collection, data analyses, and interpretation of the study data, nor were involved in the decision to publish the final manuscript. The principal investigators and authors had complete scientific freedom.